The Importance of Predictability in the Early-Life Environment for Neurodevelopment and Mental Health - Mason Hardy; Tallie Z. Baram (Annual Review of Developmental Psychology, 2026)
Predictability, the degree to which environmental inputs are structured, patterned, and reliably signaled over time, has emerged as a central dimension of early experience with unique implications for brain development, stress physiology, and mental health. This review synthesizes convergent evidence from human and animal studies to argue that predictability is intrinsic to optimal brain development. Thus, unpredictable signals from the proximate environment—parents, family, and neighborhood—are a type of early-life adversity that is distinct from, for example, threat or deprivation. We first delineate what predictability means in developmental science, distinguishing it from valence and intensity. We then summarize multilevel mechanisms, from epigenomic regulation to circuit-level adaptions, by which predictable versus unpredictable signals shape developmental trajectories. We consider predictable structure against the backdrop of established types of early-life adversity, examining how resource scarcity, caregiver stress, and chaotic routines create unpredictable patterns that link to childhood and adult psychopathology. Building on conceptual and methodological work in human study cohorts and large populations as well as experimental animals, we discuss how to measure unpredictability (e.g., signal entropy, ecological assessments, questionnaires) and highlight sensitive windows when predictability is crucial for brain maturation. Finally, we propose paths for translational research and prevention of unpredictability-related sequelae on cognitive and mental health.